Assessment of the Structure Failure of the Palm Oil Mill Effluent (POME) Digestion Tank Constructed on Peat Soil - Yusuf, Khairullah; Sulaiman, Shahlin; Suleiman, Shan (International Journal of Engineering and Technology, 2018)
The structure for extraction processes of palm oil were constructed on peat soil. Piles were commonly adopted for the foundation of such structure to transfer the imposed load to the hard layer of the soil. This study aims to investigate the probable cause of two POME digestion tanks failure at one of extraction processes of palm oil. One of the two tanks collapsed during filled up the tank with the POME and another one shows the symptom of structural failure. Based on visual inspection and analytical study, it is most likely that the failure mechanism of the POME digestion tanks is due to the deviation of the piles that induced moment onto the piles, which exceeded the structural allowable moment of the piles. There is also a possibility that the collapsed tank has been loaded to the point where piles were carrying an axial load that exceeded the said pile bearing capacity.